MORLACHISM AS AN IMAGOLOGICAL EXPERIMENT IN THE NOVEL “MLADENKA KOSTONOGA” BY ŽELIMIR PERIŠ (Philological Studies, 2025)
This paper presents an analysis of the novel Boney-legged Bride by the Croatian writer Želimir Periš through the dichotomy of morlachism. This dichotomy involves a condescending attitude toward the inferior Other – most frequently seen from the perspective of a Western, “civilized” individual toward someone from the East. Such an attitude is typically illustrated by ascribing a particular ethnic name to that inferior Other. The second element of the morlachism dichotomy is the portrayal of the culture and customs of the Slavic population of the Adriatic hinterland, modeled on the travelogue Travel to Dalmatia by Abbot Alberto Fortis. This includes descriptions of their superstitions (witches, vampires, etc.), historical-cultural phenomena such as hajduks and blood feuds, as well as folk customs that emphasize decasyllabic verses and folk singing accompanied by the gusle. This work seeks to demonstrate how the author grounds his entire novel in the dichotomy of morlachism through imagological concepts of hetero-representations and auto-representations. Through these experimental approaches, the author subjects both the kinship and identity of the superior and inferior to irony, as well as his own identity as an author. He further satirizes the relationship of that Other – whose cultural framework encompasses both the author and the reader – with respect to their own culture and tradition, achieving this through narrative methods as well as various plays with style, language, and other literary techniques.
Keywords: imagology, Identity, Alterity, Morlack, Postmodernism